Analisis Strategi Pemasaran Menggunakan Business Model Canvas dalam Meningkatkan Penjualan (Studi pada UMKM Bobabox Medan) - Afridayana; Feby Aulia Safrin (Regress: Journal of Economics & Management, 2022)
This article aims to understand Bobabox's marketing strategy using the Business Model Canvas and provide an alternative strategy design to increase sales and expand Bobabox's market using the business model canvas. This research uses a qualitative approach with a descriptive type of research. Primary data collection techniques through interviews and secondary data collection through documentation. The data analysis process is carried out by presenting data, reducing, then drawing conclusions. The results of this study are to provide an alternative strategy using the business model canvas against Bobabox in increasing sales. Then create consumer awareness in recognizing the Bobabox brand which is made by yourself or homemade from natural ingredients by carrying out marketing strategies to get closer to consumers through channels created in the process of delivering products to consumers.